Out of Europe: How English Clerics Pioneered the Concept of 'World Literature'. Issue 3 (2nd July 2020) - During, Simon
ABSTRACT: When Goethe coined the phrase 'world literature', he did so after reading a translation of a relatively obscure seventeenth-century Chinese novel, Hao Kiou Choaan. That novel had come to Europe's attention via an English translation which had been edited and published by the English clergyman Thomas Percy in 1761, before being translated in turn into French, German and Dutch. As such, Hao Kiou Choaan was one of the earliest of a series of editions and translations from all over the world that Percy put into print across the 1760s and 1770s, and which did indeed help ground the European idea of 'world literature'. This article describes the background to Percy's labours and argues that they are best understood within the context of an Anglican attempt to maintain the force of prophecy and literature's authority by uncovering how literature worked outside of European modernity.